Combination of Warm Compress and Woolwich Massage on Breast Milk Production in Post Sectio Caesarea Mothers in the Melati Room 2a Dr. Hospital Soekardjo, Tasikmalaya City - Tetet Kartilah, Tetet Kartilah; Sofia Februanti, Sofia Februanti; Novi Indriani, Novi Indriani; Peni Cahyati, Peni Cahyati; Syaukia Adini, Syaukia Adini (Jurnal Medika Cendikia, 2025)
Breastfeeding a baby is the next stage after giving birth. Previous research shows that giving exclusive breast milk can meet the baby's nutritional needs. However, many postpartum mothers still have difficulty breastfeeding properly and easily. The World Health Organization (WHO) states that 46% of new mothers experience difficulty in providing exclusive breastfeeding. Therefore, efforts that can be made to facilitate breast milk production are through massage by applying a combination technique of warm compresses with Woolwich massage which can stimulate the release of the hormones prolactin and oxytocin which influence the smooth production of breast milk. The purpose of writing this scientific paper is to provide care. Nursing for Post-Section Caesarean mothers in increasing the flow of breast milk by providing a combination technique of warm compresses with Woolwich massage. This action was carried out for 3 days, starting from 17 to 19 November 2023. The final result after being given a combination of warm compresses and Woolwich massage, both respondents experienced changes in the smoothness of breast milk production. Respondent 1 had a pre-intervention score of 0 and post-intervention had a final score of 3 (poor breast milk production), while respondent 2 had a pre-intervention score of 0 and post-intervention with a final score of 6 (good breast milk production). The conclusion of this scientific paper is that Woolwich massage can influence the increase in the smooth production of breast milk in post partum mothers, caesarean section.